Unraveling the reaction mechanism of selective C9 monomeric phenols formation from lignin using Pd-Al2O3-activated biochar catalyst - Gurrala, L.; Kumar, M. M.; Yerrayya, Attada; Kandasamy, Prabu; Castano, Pedro; Raja, T.; Pilloni, Giovanni; Paek, C.; Vinu, R. (Bioresource Technology, 2022)
The conversion of biomass-derived lignin to valuable monomeric phenols at high selectivity is of paramount importance for sustainable biorefineries. In this study, a novel Pd-Al2O3 supported on activated biochar catalyst is developed for lignin hydrogenolysis. The catalyst characterization revealed that the (1 1 1) planes of both of Pd-0 and Al2O3 were exposed to the surface. The maximum lignin conversion of 70.4% along with high liquid yield (similar to 57 wt%) was obtained at 240 degrees C, 3 h and 3 MPa H-2 pressure. The total monomeric phenols yield in the liquid was 51.6 wt%, out of which C9 monomeric guaiacols constituted similar to 30.0 wt% with 38.0% selectivity to 4-propyl guaiacol. Using the reaction intermediate, coniferyl alcohol, chemoselective hydrogenation of C-alpha=C-beta is proved to occur over the Pd site, while dehydroxylation of C-gamma-OH is shown to occur over the alumina site. An impressive carbon atom economy of 60% was achieved for the production of monomeric phenols.
Keywords: Hydrogenolysis; lignin; Mechanism; Pd-Al/activated biochar; Propanol guaiacol; Propyl guaiacol